FACTORS INFLUENCING GREEN HOME APPLIANCE PURCHASE INTENTION AMONG CONSUMERS IN RIAU ISLANDS - Ariyanto, Hepy Hefri; Syahputra, Ulung; Putra, Edy Yulianto (JMK (Jurnal Manajemen dan Kewirausahaan), 2026)
The main factors influencing consumers' inclinations to buy energy-efficient household equipment in Indonesia's Riau Archipelago are examined in this study. The study assesses the contributions of consumer attitudes, subjective norms, environmental awareness, eco-labeling, governmental laws, and willingness to pay a premium by using the Theory of Planned Behavior (TPB) framework with expanded variables. The results of a quantitative survey with 481 participants and multiple regression analysis show that government regulations, consumer attitudes, and willingness to pay all have a significant and beneficial impact on consumers' intentions to make green purchases. On the other hand, eco-labeling, environmental knowledge, and subjective norms have no discernible impact. These results highlight the role that human attitudes and public policies play in influencing sustainable purchasing patterns, offering useful information for companies and legislators looking to advance green technologies.